2013
DOI: 10.1177/0192636512473507
|View full text |Cite
|
Sign up to set email alerts
|

The Enemy Among Us

Abstract: In the United States, students with disabilities are disproportionately exposed to exclusionary discipline. Using Intergroup Threat Theory, literature was analyzed to identify expressed perceptions from school administrators that indicated perceived threat. Analysis revealed perceived threats to administrator beliefs, values, job performance, and available resources for themselves and their school communities. Intervention to alleviate this perception of threat should seek to expand administrators’ knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…While the intent of administrators who implement exclusionary discipline policies may be to maintain a safe school environment (Williams, Pazey, Shelby, & Yates, 2013) and to encourage alternative prosocial behaviors (Sharkey & Fenning, 2012), there is substantial “evidence that such policies are neither effective nor implemented in a manner that is child centered or equitable” (Verdugo, 2002, p. 51). With regard to efficacy, these practices result in more administrative time being devoted to handling school discipline, lost instructional minutes, and lower scores on achievement tests (Losen, 2011; Sharkey & Fenning, 2012).…”
Section: General Overview Of Exclusionary Disciplinementioning
confidence: 99%
See 1 more Smart Citation
“…While the intent of administrators who implement exclusionary discipline policies may be to maintain a safe school environment (Williams, Pazey, Shelby, & Yates, 2013) and to encourage alternative prosocial behaviors (Sharkey & Fenning, 2012), there is substantial “evidence that such policies are neither effective nor implemented in a manner that is child centered or equitable” (Verdugo, 2002, p. 51). With regard to efficacy, these practices result in more administrative time being devoted to handling school discipline, lost instructional minutes, and lower scores on achievement tests (Losen, 2011; Sharkey & Fenning, 2012).…”
Section: General Overview Of Exclusionary Disciplinementioning
confidence: 99%
“…Second, with regard to exclusionary practices not being child centered or equitable, administrators often rely on personal discretion (Williams et al, 2013) in discipline cases, which opens the door for multiple interpretations, particularly in relation to offenses that are subjective judgment calls. This issue was underscored in a study conducted by Skiba, Peterson, and Williams (1997) who found that administrators in one school varied in their interpretation of what defined defiant behavior.…”
mentioning
confidence: 99%